2022
DOI: 10.7759/cureus.29491
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Renal Vein Thrombosis Associated With COVID-19 Treated With Rivaroxaban

Abstract: Renal vein thrombosis (RVT) is a rare form of deep venous thrombosis. It usually involves one or both renal veins and one of their branches. Most cases were reported in patients with nephrotic syndrome or inherited hypercoagulability syndromes. RVT can present with flank pain, hematuria, and acute kidney injury but can also present asymptomatically and be incidentally discovered on abdominal or renal imaging. The management of RVT is usually with warfarin for at least six to 12 months and periodically is conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…COVID-19 has also been associated with some cases of RVT, which is attributed to the ability of the virus to cause direct harm to the endothelium and trigger an overactive inflammatory response [ 1 , 2 ]. There have been documented case reports highlighting the occurrence of RVT in patients diagnosed with COVID-19 [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 has also been associated with some cases of RVT, which is attributed to the ability of the virus to cause direct harm to the endothelium and trigger an overactive inflammatory response [ 1 , 2 ]. There have been documented case reports highlighting the occurrence of RVT in patients diagnosed with COVID-19 [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In concordance with other studies, our case shows that RVT may be a consequence of COVID-19 infection or even a feature of long COVID. Other types of DOACs, such as Rivaroxaban, have shown positive results in treating RVT in single case studies ( 16 , 24 ). To the best of our knowledge, our study is the first to have used Apixaban as a treatment for a rare presentation of RVT in the renal arcuate veins.…”
Section: Discussionmentioning
confidence: 99%
“…Apixaban has been formerly shown as a reliable drug in treating venous thromboembolism. A randomized clinical trial of 5395 participants concluded that Apixaban therapy did not show inferior results compared to conventional therapy in venous thromboembolism patients (23). One of the few studies regarding DOACs treatment in the setting of VTE in atypical locations demonstrated that there were no statistically significant differences in VTE recurrence and hemorrhage risk between those treated with DOACs such as Rivaroxaban/Apixaban and those conventionally treated with low molecular weight Heparins such as Enoxaparin (14).…”
Section: Discussionmentioning
confidence: 99%